ANALISIS KANDUNGAN SULFORAFAN PADA BEBERAPA FASE PERTUMBUHAN DARI BEBERAPA JENIS BRASSICACEAE - W. ., Tilaar; J. Polii Mandang; A. ., Pinaria (EUGENIA, 2022)
The purpose of this research was to determine differences in sulforaphane content in sprouts, cauliflower seedlings, mature plants from white flower cabbage, broccoli, cabbage and Chinese cabbage. This research was conducted in Tomohon and analyzed in the Chemistry laboratory of the State Polytechnic of Malang. The research method used was a randomized block design with 4 treatments, namely broccoli, white cauliflower, rock cabbage and Chinese cabbage with 3 repetitions in each growth phase. The results of the analysis of sulforaphane content in the growth phase of sprouts were the highest in broccoli, which was 117.08 ug, higher than white cauliflower (0.72 ug), rock cabbage (16.58 ug) and Chinese cabbage 0.38 ug). Furthermore, in the young plant phase the highest sulforaphane content in broccoli was 0.679 ug compared to white cauliflower (0.018 ug), rock cabbage (0.183 ug), and Chinese cabbage (0.003 ug). Then lastly, the highest sulforaphane content in mature plants was rock cabbage, which was 0.776 ug compared to broccoli (0.148 ug), white cauliflower (0.273 ug), and Chinese cabbage (0.001 ug). So the sulforaphane content in the sprouting phase of broccoli was higher than that of white cauliflower, rock cabbage and cabbage sprouts. Similarly, in young plants and in mature plants, rock cabbage showed higher sulforaphan content.